Between Obsessive-Compulsive Disorder and Psychosis - Marques,Mafalda Castro (2022)
Abstract Introduction: Obsessive-compulsive disorder is an heterogeneous condition in which periods of altered perception or delusions may arise. Similarly, individuals with psychotic disorders may have obsessive-compulsive symptoms. Case report: A male adolescent presented to the Emergency Department (ED) with obsessive symptomatology with three months of evolution. Three weeks later, he returned to the ED showing symptom worsening and reporting delusions, being admitted to the inpatient unit to clarify the diagnosis. No positive symptoms were reported during hospitalization. During follow-up, the patient reported an episode of apparent delusional perception that he associated with the beginning of symptoms, again raising the question of whether a psychotic episode was present. Discussion/Conclusions: The distinction between obsessive-compulsive disorder and psychosis is not always clear, with obsessive-compulsive disorder being a significant comorbidity in patients with a first psychotic episode. Close patient assessment is required for early diagnosis and appropriate intervention.